Pengaruh Edukasi Kesehatan Metode Demonstrasi dan Leaflet terhadap Kemampuan dan Pengetahuan Praktik SADARI pada Remaja Putri di SMAN 2 Banjarmasin - Annisa Maryam; Yenny Okvitasari; Zaiyidah Fathony; Kristina Yuniarti (Yayasan Literasi Sains Indonesia, 2026)
Adolescent girls are a group vulnerable to limited knowledge and practice ability of Breast Self-Examination (BSE), therefore effective health education is needed as an early detection effort for breast cancer. In 2023, Banjarmasin became the city with the highest number of breast cancer cases, totaling 36 cases. Leaflet media and demonstration methods are educational approaches that are easily applied in the school environment; however, their effectiveness in improving knowledge and practice ability of BSE needs to be scientifically proven. This study aimed to determine the effect of health education using leaflets and demonstration methods on the knowledge and practice ability of BSE among adolescent girls. This study employed a pre-experimental design with a one-group pretest–posttest approach. Data analysis was conducted using the Wilcoxon Signed Rank Test with a significance level of 0.05. The results showed an increase in knowledge and practice ability of BSE after health education was provided. The Wilcoxon test showed a significance value of p < 0.001, indicating a statistically significant difference in knowledge and practice ability of BSE before and after the intervention. In conclusion, health education using demonstration methods and leaflets has a significant effect on improving knowledge and practice ability of BSE among adolescent girls.